Chemical composition, antiproliferative and antioxidant attributes of ethanolic extract of resinous sediment from Etlingera elatior (Jack.) inflorescence - Majed Ahmed Al-Mansoub; Muhammad Asif; Vageesh Revadigar; Mohamed A. Hammad; Nelson Jeng-Yeou Chear; Mohammad Razak Hamdan; Amin Malik Shah Abdul Majid; Mohd Zaini Asmawi; Vikneswaran Murugaiyah (Universidade de São Paulo, 2021)
The ethanolic extract of resinous sediment (EERS) of Etlingera elatior young inflorescence was examined for its anticancer effect and potential antioxidant activity. The anticancer effect of the EERS was evaluated on four human cancer cell lines, HCT 116, HT-29, Hela, and MCF-7, using the MTT assay. GC-MS analysis showed that the main components found in the EERS were nonyl cyclopropane (4.44%), 1-tetradecane (3.66%), cyclotetradecane (2.41%), cyclododecane (1.92%), and 1-decene (1.72%). The antioxidant activity was determined through different methods. High amounts of TPC and TFC in the EERS were found. Moderate antioxidant capacity of the EERS was detected by DPPH and ABTS assays, with EC50 values of 44.19 and 56.61 μg/mL and a high FRAP value of 281.79 nmol Fe+2 equivalent/mg extract. In the MTT assay, the EERS showed potent anticancer activity, with IC50 values of 19.82, 37.001, 50.49, and 53.29 μg/mL against HT-29, HCT 116, Hela, and MCF-7 tumour cell lines, respectively. Moreover, the results were comparable to or less potent than the standard reference drug, 5-fluorouracil. The results showed that the EERS of Etlingera elatior inflorescence contained a high amount of polyphenols and flavonoids, which may to the selective antiproliferative effects towards colon cancer in vitro